Pengaruh Pertumbuhan Ekonomi dan Pertumbuhan Angkatan Kerja Terhadap Tingkat Pengangguran Di Kota Pekalongan - Pratomo Cahyo Kurniawan; Nala Khilmiana; Sandi Arifin; Asih Maisaroh (Program Studi Manajemen Universitas Muhadi Setiabudi, 2023)
Economic growth is usually used as a reference as an indicator of economic success in a region. Such indicators are, for example, problems regarding inflation and unemployment as well as improving public welfare. One of the factors that influence economic growth is the number of labor force and unemployment. From year to year population growth is relatively increasing and it will also affect the growth of the labor force. In urban areas, the growth of the labor force is relatively increasing from year to year. In the city of Pekalongan, there is still an alarming number of unemployed, which is 11.042.00 people in 2020. This study aims to determine the effect of economic growth and labor force growth on the unemployment rate in the city of Pekalongan. This type of research is descriptive analytical quantitative research. Analytical descriptive quantitative is a technique or method used is descriptive analytical quantitative method, analytical descriptive method is a method that functions to obtain in-depth data. The point is which data contains meaning and can affect the substance of significant research. Data collection was obtained from secondary data taken from the Central Statistics Agency of Pekalongan City. Based on the results of this study, the level of the labor force and unemployment will also affect the level of economic growth. So that the data obtained from BPS is certainly valid, so it can be concluded that economic growth in Pekalongan City is relatively low, because based on data from BPS Pekalongan City, the number of labor force and unemployment is still relatively high.